Uncovering the Hidden Curriculum in Health Professions Education - Laura L. Wolford; Mirza J. Lugo-Neris; Callie Watkins Liu; Lexi E. Nieves; Christopher L. Rodriguez; Siya S. Patel; Sol Yi Lee; Keshrie Naidoo (Education Sciences, 2025)
In health professions education, the hidden curriculum is a set of implicit rules and expectations about how clinicians act and what they value. In fields that are very homogenous, such as rehabilitation professions, these expectations may have outsized impacts on students from minoritized backgrounds. This qualitative study examined the hidden curriculum in rehabilitation graduate programs—speech-language pathology, occupational therapy, and physical therapy—through the perspectives and experiences of 21 students from minoritized backgrounds. Semi-structured interviews explored their experiences with their programs’ hidden curricula. These revealed expectations about ways of being, interacting, and relating. Three overarching themes emerged, each reflecting tensions between conflicting values: (i) blend in but stand out; (ii) success lies in individualism, while de-prioritizing the individual; and (iii) fix the field, using your identities as a tool. When the expectations aligned with students’ expectations for themselves, meeting them was a source of pride. However, when the social expectations clashed with their own culture, dis/ability, gender, or neurotype, these tensions became an additional cognitive burden, and they rarely received mentorship for navigating it. Health professions programs might benefit from fostering students’ critical reflection on their hidden curricula and their fields’ cultural norms to foster greater belonging, agency, and identity retention.